Differential impairment of spatial location memory in Huntington's disease. Issue 11 (14th October 2005) - Brandt, J; Shpritz, B; Munro, C A; Marsh, L; Rosenblatt, A
Abstract : Objective: To determine whether a differential impairment of spatial memory exists in Huntington's disease (HD). Methods: Patients with HD and age matched neurologically normal subjects, as well as patients with Alzheimer's disease (AD) and Parkinson's disease (PD), learned the locations of nine items on a 3×3 grid over as many as 10 trials. Delayed recall of the items and their spatial locations was tested. Results: Patient with HD performed worse than normal subjects on all measures, and intermediate between AD and PD patients. However, they were the only subject group in whom delayed recall of spatial locations was poorer than delayed recall of object identity. This effect was independent of the severity of dementia. Conclusions: HD patients have a differential impairment in memory for object–location information. This finding may relate to the involvement of the caudate nucleus, the primary site of pathology in HD, in corticostriatal circuits linking it with parietal association cortex. It is also consistent with views of the dorsal striatum as responsible for the acquisition over trials of specific place responses.